Down-Regulation of Placental Transport of Amino Acids Precedes the Development of Intrauterine Growth Restriction in Maternal Nutrient Restricted Baboons - Pantham, Priyadarshini (Biol Reprod, 2016)
Intrauterine growth restriction (IUGR) is an important risk factor for perinatal complications and adult disease. IUGR is associated with down-regulation of placental amino acid transporter expression and activity at birth. It is unknown whether these changes are a cause or a consequence of human IUGR. We hypothesized that placental amino acid transport capacity is reduced prior to onset of reduced fetal growth in baboons with maternal nutrient restriction (MNR). Pregnant baboons were fed either a control (n = 8) or MNR diet (70% of control diet, n = 9) from Gestational Day 30. At Gestational Day 120 (0.65 of gestation), fetuses and placentas were collected. Microvillous (MVM) and basal (BM) plasma membrane vesicles were isolated. System A and system L transport activity was determined in MVM, and leucine transporter activity was assessed in BM using radiolabeled substrates. MVM amino acid transporter isoform expression (SNAT1, SNAT2, and SNAT4 and LAT1 and LAT2) was measured using Western blots. LAT1 and LAT2 expression were also determined in BM. Maternal and fetal plasma amino acids concentrations were determined using mass spectrometry. Fetal and placental weights were unaffected by MNR. MVM system A activity was decreased by 37% in MNR baboon placentas (P = 0.03); however MVM system A amino acid transporter protein expression was unchanged. MVM system L activity and BM leucine transporter activity were not altered by MNR. Fetal plasma concentrations of essential amino acids isoleucine and leucine were reduced, while citrulline increased (P < 0.05) in MNR fetuses compared to controls. In this primate model of IUGR, placental MVM system A amino acid transporter activity is decreased prior to the onset of reduction in the fetal growth trajectory. The reduction in plasma leucine and isoleucine in MNR fetuses may be caused by reduced activity of MVM system A, which is strongly coupled with system L essential amino acid uptake. Our findings indicate that reduced placental amino acid transport may be a cause rather than a consequence of IUGR due to inadequate maternal nutrition.